1976
DOI: 10.1139/v76-449
|View full text |Cite
|
Sign up to set email alerts
|

Acid dissociation constants and rates as studied by ultrasonic absorption

Abstract: Experimental ultrasonic absorption data on solutions of H2SO4 and H3PO4 are interpreted in terms of proton transfer equilibria. The acid dissociation constants obtained are compared with those obtained using other methods and are shown to be consistently lower. A model is proposed to explain this in terms of ΔVθ and ΔHθ involved in the steps leading to recombination of the proton with the anion. This model is supported by the values of the reaction distance parameters calculated from the value of the rate cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…However, we found only one study in which the proton dissociation rate of H 3 PO 4 was reported, with a value of k f,1 = 3.8 × 10 8 s −1 measured via ultrasonic absorption. 66 We used this value to determine the corresponding protonation rate constant k r,1 via the equilibrium constant K = k f /k r , the values for which are readily available in the literature (see the Supporting Information, Table S5). Thus, we were left with two unknown protonation/ deprotonation rate constants: one for H 2 PO 4 − and another for HPO 4 2− .…”
Section: ■ Discussionmentioning
confidence: 99%
“…However, we found only one study in which the proton dissociation rate of H 3 PO 4 was reported, with a value of k f,1 = 3.8 × 10 8 s −1 measured via ultrasonic absorption. 66 We used this value to determine the corresponding protonation rate constant k r,1 via the equilibrium constant K = k f /k r , the values for which are readily available in the literature (see the Supporting Information, Table S5). Thus, we were left with two unknown protonation/ deprotonation rate constants: one for H 2 PO 4 − and another for HPO 4 2− .…”
Section: ■ Discussionmentioning
confidence: 99%
“…present. [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] The first dissociation equilibrium of the phosphoric acid:…”
Section: Introductionmentioning
confidence: 99%
“…7 used in the analysis. It is of interest to note that y, varies relatively little with the value of Kt, due to counterbalancing effects in [5]. The p used and they, calculated here do not assume complete dissociation as some listings do.…”
Section: Correlation Of Ultrasonic and Conductivity Resultsmentioning
confidence: 94%
“…Next the degree of dissociation cr can be obtained, and hence the ionic strength p = crc for a 1 : 1 electrolyte. They, is next calculated from [5] and a new value Kc = y k 2 K,, is obtained. This iteration is continued until Kc is constant to within 0.1%.…”
Section: Correlation Of Ultrasonic and Conductivity Resultsmentioning
confidence: 99%